Preparation method of rapidly-solidified iron-based alloy strip

By combining precision balance and high vacuum induction smelting belt swing machine, appropriate process parameters are set, which solves the problem that the process parameters do not form standards in the preparation of low alloy steel strips, and realizes the efficient preparation of fast solidification iron-based alloy strips and Improved mechanical properties.

CN119259932AActive Publication Date: 2025-01-07NAVAL UNIV OF ENG PLA
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411029880.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-07-30
Publication Date
2025-01-07
Estimated Expiration
2044-07-30

AI Technical Summary

Technical Problem

There are few researches on the preparation of medium and medium- and low alloy steel strips in the prior art, no standard is formed, and most of them rely on operating experience, making it difficult to achieve efficient preparation of fast solidification iron-based alloy strips.

Method used

Use precision balances to weigh electrolytic iron, single crystal silicon and iron trioxide, and use a high vacuum induction smelting belt swing machine to perform induction smelting and cooling belt swing, setting the appropriate copper wheel speed, injection pressure and nozzle to copper wheel distance. Ensure accurate proportioning and rapid solidification of alloy components.

Benefits of technology

The rapid solidification of the alloy is achieved, the structure is significantly refined, the mechanical properties of the material are improved, and the operation experience is not required, which improves the production standardization.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119259932A_ABST
    Figure CN119259932A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of alloy preparation, and discloses a preparation method of a rapidly solidified iron-based alloy strip, which comprises the following steps: weighing electrolytic iron, monocrystalline silicon, carbon powder and ferric oxide, carrying out vacuum melting, repeatedly melting and cooling to obtain as-cast master alloy; cutting out mother alloy, placing the mother alloy in a quartz tube, and smelting and melt-spinning the mother alloy according to specific parameters to prepare the rapidly-solidified iron-based alloy strip. The preparation parameters of the Fe-O lacing sample are set as follows: the rotating speed of a copper wheel is 2050r / min, the injection air pressure is 0.002 MPa, and the distance from a nozzle to the copper wheel is 0.02 mm; the preparation parameters of the Fe-S i-C-O lamellar sample are set as follows: the rotating speed of a copper wheel is 2400 r / min, the injection air pressure is 0.004 MPa, and the distance from a nozzle to the copper wheel is 0.03 m, so that the accurate proportioning of alloy components is ensured, and the chilling melt-spinning function of a high-vacuum induction melting melt-spinning machine is utilized, so that the rapid solidification of the alloy is realized, the alloy structure is obviously refined, the mechanical property of the material is improved, and the production cost is reduced. And the method does not need to depend on experience summary of operators, and the standardization during production is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of metal preparation, and in particular relates to a method for preparing a rapidly solidified iron-based alloy strip. Background Art

[0002] Regarding how to change the state of oxygen in steel, studies have shown that rapid cooling can effectively inhibit the precipitation of oxygen in the form of oxide inclusions, promote the solid solution of oxygen in the steel in the form of atoms, and help increase the content of dissolved oxygen in the steel. However, due to the limitations of technological development, the current preparation of rapid cooling samples is mostly strip samples or small block samples, and researchers are more focused on the preparation of multi-component medium and high alloy steel strips. However, there are relatively few studies on the preparation of low-alloy steel strips under quenching, and the relevant process parameters have not yet formed standards, mostly relying on the operator's experience summary. Therefore, a method for preparing rapidly solidified iron-based alloy strips is proposed to solve the above problems. Summary of the invention

[0003] The object of the present invention is to provide a method for preparing a rapidly solidified iron-based alloy strip to solve the problems raised in the above background technology.

[0004] To achieve the above object, the present invention provides the following technical solution: a method for preparing a rapidly solidified iron-based alloy strip, comprising:

[0005] S1: Weigh the preset mass of electrolytic iron, single crystal silicon, carbon powder and ferric oxide by a precision balance;

[0006] S2: Put the material into the container, then put the container into the induction coil of the smelting belt throwing equipment, and evacuate the vacuum until the vacuum degree is less than 5×10 -5 Pa, stop vacuuming and fill with argon for protection;

[0007] S3: Induction melting is performed through an induction coil. After the material inside the container is completely melted, it is kept warm for a preset time, and then the molten steel is poured into the mold through an operating rod. It is taken out after cooling to room temperature. Before taking out the sample, the vacuum chamber is always kept in an argon protection state;

[0008] S4: After repeating S2 to S3 three times, the material inside the mold forms Fe-SiCO and Fe-O cast master alloys. 10g of Fe-Si-CO and Fe-O cast master alloys are cut and placed in a special quartz tube for belt spinning, and the special quartz tube for belt spinning is placed in a melting belt spinning equipment for melting. The parameters for preparing the Fe-O belt sample are: copper wheel speed 2050r / min, injection air pressure 0.002MPa, and distance from nozzle to copper wheel 0.02mm; the parameters for preparing the Fe-SiCO belt sample are: copper wheel speed 2400r / min, injection air pressure 0.004MPa, and distance from nozzle to copper wheel 0.03mm, and the rapidly solidified Fe-Si-CO and Fe-O belt samples are prepared by the quenching belt spinning function.

[0009] Preferably, the mass percentage of the electrolytic iron is 99.99%, the mass percentage of the single crystal silicon is 99.99%, the mass percentage of the carbon powder is 99.99%, and the mass percentage of ferric oxide is 99.99%.

[0010] Preferably, the ultimate vacuum degree of the smelting belt-swinging equipment is not less than 7×10 -4 Pa, the maximum smelting power is 35KVA, and the induction frequency is 30~80KHz.

[0011] Preferably, the melting and belt-spinning equipment is a JVSM-2 high vacuum induction melting and belt-spinning machine.

[0012] Preferably, the precision of the precision balance is 0.0001 mg.

[0013] Preferably, the inner cavity size of the mold is

[0014] Preferably, in S2, the argon protection pressure is -0.06 MPa.

[0015] Preferably, in S3, the preset duration is five minutes.

[0016] Preferably, the container is a magnesium oxide crucible.

[0017] Preferably, the mold is a copper mold.

[0018] Compared with the prior art, the present invention has the following beneficial effects:

[0019] The invention adopts a high-precision balance to weigh raw materials, and sets the parameters for preparing the Fe-O banded sample as follows: a copper wheel rotation speed of 2050 r / min, a jet air pressure of 0.002 MPa, and a distance from the nozzle to the copper wheel of 0.02 mm; and sets the parameters for preparing the Fe-SiCO banded sample as follows: a copper wheel rotation speed of 2400 r / min, a jet air pressure of 0.004 MPa, and a distance from the nozzle to the copper wheel of 0.03 m, thereby ensuring the precise proportion of alloy components, utilizing the chilling and strip-spinning function of a high vacuum induction melting and strip-spinning machine, realizing rapid solidification of the alloy, significantly refining the alloy structure, and improving the mechanical properties of the material, without relying on the experience summary of operators, thereby improving standardization during production. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 It is a structural schematic diagram of the present invention;

[0021] Figure 2 This is a schematic diagram of the test results of the alloy composition distribution of the present invention;

[0022] Figure 3 This is a sample diagram of the present invention under different injection pressures;

[0023] Figure 4 The sample diagram of the copper wheel of the present invention at different rotation speeds;

[0024] Figure 5 The strip sample diagram obtained at different spraying distances of the present invention;

[0025] Figure 6 This is a strip sample image obtained after the parameters are improved according to the present invention. DETAILED DESCRIPTION

[0026] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0027] See also Figure 1-Figure 6 As shown, the present invention provides the following technical solution: a method for preparing a rapidly solidified iron-based alloy strip, comprising:

[0028] S1: Weighing a preset mass of electrolytic iron, single crystal silicon, carbon powder and ferric oxide by a precision balance, the accuracy of the precision balance is 0.0001 mg. In addition, in the present invention, the mass percentage of electrolytic iron is 99.99%, the mass percentage of single crystal silicon is 99.99%, the mass percentage of carbon powder is 99.99%, and the mass percentage of ferric oxide is 99.99%. The low content of impurity elements in the electrolytic iron can effectively avoid the influence of other elements on the refined master alloy, and the smelted master alloy is mass proportioned according to 200g;

[0029] S2: Load the material into the magnesium oxide crucible, then put the magnesium oxide crucible into the induction coil of the JVSM-2 high vacuum induction melting belt-spinning machine, and evacuate the vacuum until the vacuum degree is less than 5×10 -5 Pa, stop vacuuming and fill with argon for protection, the argon protection pressure is -0.06MPa, use magnesium oxide crucible for smelting, the maximum capacity is 1000g (calculated as iron). The melting point of magnesium oxide is 2582℃, which is much higher than the melting point of iron 1538℃, which can effectively avoid the introduction of impurity elements by melting the crucible during the smelting process;

[0030] In addition, regarding the above-mentioned JVSM-2 high vacuum induction melting belt-swinging machine, the copper wheel of the equipment adopts magnetic fluid sealing technology, and its maximum rotation speed can reach 60m / sec, and the fastest cooling speed it can provide is ≥106K / sec; and the cooling speed can be adjusted by adjusting the copper wheel rotation speed, heating current and cooling water temperature. The thickness of the equipment product is 20-60μm, the width is between 1-10mm, and the maximum melting temperature is ≥1600℃. The crucible used in the belt-swinging test is a special quartz crucible, and its nozzle size is a narrow slit of 10mm long and 3mm wide. The maximum sample melting sample is 70g (in terms of iron). The equipment also has an adjustable, water-cooled crucible support, and its injection tilt angle is adjustable within the range of 0-90°.

[0031] S3: Induction melting is performed through the induction coil. After the material inside the magnesium oxide crucible is completely melted, it is kept warm for five minutes, and then the molten steel is poured into the copper mold through the operating rod. The inner cavity size of the copper mold is After cooling to room temperature, take it out. Before taking out the sample, the vacuum chamber is always kept in argon protection state. Use copper mold for casting. Copper has good thermal conductivity and can effectively shorten the cooling time of molten steel. In order to adapt to the size of magnesium oxide crucible, the master alloy made by S3 needs to be processed. The cylindrical specimens have no obvious defects on the surface of the test alloys after removing the surface defects of the parent alloy, and the surface of the Si-containing test alloy is relatively bright. Before the belt-spinning test, the ingots are ground step by step to 1000# to remove the surface oxide film, washed with deionized water, degreased with acetone, and then quickly dried. In order to avoid the oxide film on the surface of the casting sample interfering with the oxygen addition of the alloy, the casting sample needs to be polished and degreased before use;

[0032] S4: After S2-S3 are repeated three times, the material inside the copper mold forms Fe-SiCO and Fe-O cast master alloys. 10g of Fe-Si-CO and Fe-O cast master alloys are cut and placed in a special quartz tube for belt spinning, and the special quartz tube for belt spinning is placed in a JVSM-2 high vacuum induction melting belt spinning machine for melting. The parameters for preparing the Fe-O belt sample are: copper wheel speed 2050r / min, injection air pressure 0.002MPa, and distance from nozzle to copper wheel 0.02mm; Fe-Si-CO and Fe-O cast master alloys are cut and placed in a special quartz tube for belt spinning. The parameters for preparing the iCO banded samples are: copper wheel speed 2400r / min, injection pressure 0.004MPa, nozzle to copper wheel distance 0.03mm, and the rapid solidification Fe-Si-CO and Fe-O banded samples are prepared by the quenching and stripping function. Among them, there are obviously more defects on the surface of the Fe-O alloy, and the surface finish of the master alloy is poor. This is because the oxygen content in the alloy is high and it is in a boiling state during smelting, which leads to more pores in the alloy. After adding 0.6wt% of single crystal silicon, the surface of the Fe-SiCO master alloy is smoother, without obvious loose pores and other defects. This is because the silicon and carbon added to the alloy have a certain deoxidation effect, which can calm the alloy.

[0033] Furthermore, regarding the above-mentioned JVSM-2 high vacuum induction melting belt-spinning machine, the ultimate vacuum degree of the equipment is not less than 7×10 -4 Pa, the maximum smelting power is 35KVA, and the induction frequency is 30~80KHz.

[0034] In addition, in the present invention, in order to verify the uniformity of the composition distribution of the master alloy, the composition analysis of the test alloy surface is performed. Figure 2 As shown in the figure: except for the partial aggregation of carbon element, the other components are evenly distributed in the test alloy. It can be considered that the uniformity of the master alloy prepared in the test meets the test requirements.

[0035] Furthermore, in order to study the influence of the injection pressure, in the present invention, the test alloy is heated by electromagnetic induction of the energized coil in a quartz crucible, and the melting power is slowly increased from 0KVA at a rate of 0.1KVA. As the melting power is continuously increased, the steel can be observed to turn red and then emit a dazzling white light during the melting process. After it is completely melted (about 1.5KVA), the melting power is appropriately reduced to keep the molten steel boiling and keep it warm for 60s. Argon gas is introduced to apply pressure to the molten steel so that the molten steel can flow out of the nozzle evenly, contact with the copper wheel that is passed through cooling water and rotates at a high speed, cool and form on the copper wheel, and separate from the copper wheel into the sampling chamber under the action of centrifugal force. Therefore, the size of the injection pressure directly affects the contact speed between the molten steel and the copper wheel, and will have an important influence on the cooling effect under the condition of a certain cooling speed. Based on the reference to relevant research, this experiment uses high-purity electrolytic iron as raw material, fixes the copper wheel speed at 3000r / min, and the distance from the nozzle to the copper wheel is 1mm. The cooling belt is spun under the conditions of injection gas pressure of 0.04, 0.03, 0.02, 0.01, 0.005, and 0.002MPa respectively. The experimental results are as follows Figure 3 As shown, Figure 3 The first picture in the first row from the left is the sample picture under the injection pressure of 0.04MPa. Figure 3 The second picture in the first row from the left is the sample picture under the injection pressure of 0.03MPa. Figure 3 The first picture in the second row from the left is the sample picture under the injection pressure of 0.02MPa. Figure 3 The second picture in the second row from the left is a sample picture under 0.01MPa injection pressure. Figure 3 The first picture in the third row from the left is a sample picture under a jet pressure of 0.005 MPa. Figure 3 The second picture in the third row from the left is a picture of the sample under a jet pressure of 0.002 MPa.

[0036] Depend on Figure 3 It can be seen that the injection pressure has an important influence on the formability of the strip. When the injection pressure is 0.02-0.04MPa, due to the high pressure, the molten steel cannot be well contacted with the copper wheel for cooling. Some molten steel even pops out directly into the vacuum chamber and splashes on the furnace wall. The molten steel is red and the cooling effect is poor. After cooling, the sample is in the shape of dots. The samples that contact the copper wheel and enter the cooling chamber through the belt are mostly powdery, and the formability and continuity of the samples are very poor. With the reduction of injection pressure, the formability of the pure iron strip sample has been significantly improved. Among them, the sample with an injection pressure of 0.002MPa has already appeared strips, but most of them are broken strips and the width and thickness of the strips have not met the requirements. Improvements need to be made on this basis.

[0037] From the above research results, it can be seen that the injection pressure has an important influence on the formability of pure iron strip samples under quenching. The ideal strip preparation process is as follows:

[0038] 1: Under a certain injection pressure, molten steel can be ejected at a relatively uniform rate, which is conducive to the good continuity of the strip sample;

[0039] 2: The cooling degree that the copper wheel can provide per unit time just meets the cooling amount required by the amount of sample contacted by the copper wheel;

[0040] 3: The contact time between molten steel and copper wheel can ensure that the molten steel is cooled and formed and has good connectivity with subsequent samples.

[0041] Therefore, the size of the injection pressure is closely related to the formability and continuity of the strip sample. Since alloys of different compositions have great differences in liquid fluidity and cooling rate, the size of the injection pressure needs to be explored according to the specific alloy composition.

[0042] According to the above experimental results, the effect of copper wheel at different speeds on the preparation of pure iron strip samples was investigated under the condition of fixed nozzle distance and spray pressure. In the experiment, the nozzle distance was 0.1mm, the spray pressure was 0.002MPa, and the copper wheel speed was set to 1200, 1500, 1800, 2100, 2400, and 2700r / min. The experimental results are as follows: Figure 4 As shown, Figure 4 The first picture in the first row from the left is a sample picture at a pulley speed of 1200r / min. Figure 4 The second picture in the first row from the left is a sample picture at a pulley speed of 1500r / min. Figure 4 The first picture in the second row from the left is a sample picture at a pulley speed of 2100r / min. Figure 4 The second picture in the second row from the left is a sample picture at a pulley speed of 2100r / min. Figure 4 The first picture in the third row from the left is a sample picture at a pulley speed of 2400r / min. Figure 4 The second picture in the third row from the left is a sample picture at a pulley speed of 3000r / min.

[0043] According to the above experimental results, the influence of the distance between the quartz crucible nozzle and the copper wheel, i.e. the injection distance, on the preparation of pure iron strip samples was investigated under the condition of a fixed copper wheel speed of 2100r / min and an injection gas pressure of 0.002MPa. Figure 5 As shown, Figure 5 The medium spray distances are 3mm, 2mm, 1mm, 0.6mm, 0.4mm, and 0.2mm respectively.

[0044] It can be seen from the above that when the spray distance is 2mm~3mm, the sample is in the form of multiple small clumps and has poor formability; this is because when the spray distance is large, the molten steel is easy to sputter on the surface of the copper wheel, thereby interrupting the connection between the samples and making it impossible to form a continuous strip sample. By continuously reducing the distance from the nozzle to the copper wheel, the formability and continuity of the sample have been greatly improved. When the spray distance is 0.2mm~0.4mm, the sample has basically become a strip sample, and the free surface of the sample presents a bright metallic luster. However, because the sample has not been fully cooled when it leaves the copper wheel under this parameter condition, sample accumulation is likely to occur when the sample continues to cool in the sampling chamber, and entanglement occurs between the strips. The relevant experimental parameters need to be further optimized and improved.

[0045] On the basis of the above experiments, the experimental parameters were further optimized through repeated tests, and finally the optimal parameters for the preparation of high-purity electrolytic iron strip samples under rapid cooling were determined to be: copper wheel speed 2050r / min, jet gas pressure 0.001MPa, and jet distance 0.03mm. On the basis of this experiment, Fe-Si-CO and Fe-O iron-based low alloy steel strip samples were prepared under quenching. The parameters for the preparation of Fe-O strip samples were: copper wheel speed 2050r / min, jet gas pressure 0.002MPa, and the distance from the nozzle to the copper wheel was 0.02mm; the parameters for the preparation of Fe-SiCO strip samples were: copper wheel speed 2400r / min, jet gas pressure 0.004MPa, and the distance from the nozzle to the copper wheel was 0.03mm. The prepared D1 and D6 strips are shown in the figure. Figure 6 As shown in the figure, the sample has basically formed into a strip shape, but there is still a phenomenon of strip sample agglomeration. From it, a relatively complete strip can be peeled off for electrochemical test. In order to further improve the formability and integrity of the strip, the process parameters can be improved and improved by considering the influence of other factors on the strip sample preparation. Specifically, improvements can be made in the following two aspects:

[0046] (1) Consider lowering the temperature of the cooling medium. For example, adding industrial ice cubes to the cooling water tank can effectively improve the cooling effect of the copper wheel and complete the cooling of the molten steel before it leaves the copper wheel.

[0047] (2) Design the composition of the material. For example, relevant studies have shown that adding the element B can effectively reduce the driving force required for cooling steel.

[0048] As can be seen from the figure, when the speed is 1200 and 1500r / min, the sample tends to shrink into a ball. This is because the cooling degree provided by the copper wheel at low speed is not enough to cool the molten steel when it leaves the copper wheel; the sample flies out in the form of a parabola and accumulates in the sampling chamber under the action of centrifugal force. During the test, it was observed that the temperature of the outer wall of the sampling chamber was high, which also proved this point. When the speed is 2400 and 2700r / min, the samples are mostly powdery and small blade-shaped. This is because the cooling capacity provided by the copper wheel at high speed exceeds the cooling degree required for the sample volume per unit time, and the contact time between the molten steel and the copper wheel at high speed is shortened, and turbulence may even occur; the small blade-shaped samples are mostly because the molten steel contacts the copper wheel in the form of small droplets, which makes the sample not very continuous. When the rotation speed is 1800 and 2400r / min, the sample has good formability and continuity, especially when the rotation speed is 2100r / min, the sample has some banding and the surface has a metallic luster, but the continuity of the banding needs to be improved.

[0049] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing a rapidly solidified iron-based alloy strip, characterized in that: include, S1: Weigh the preset mass of electrolytic iron, single crystal silicon, carbon powder and ferric oxide by a precision balance; S2: Put the material into the container, then put the container into the induction coil of the smelting belt throwing equipment, and evacuate the vacuum until the vacuum degree is less than 5×10 -5 Pa, stop vacuuming and fill with argon for protection; S3: Induction melting is performed through an induction coil. After the material inside the container is completely melted, it is kept warm for a preset time. Then the molten steel is poured into the mold through an operating rod. After cooling to room temperature, it is taken out. Before taking out the sample, the vacuum chamber is always kept in an argon protection state; S4: After repeating S2 to S3 three times, the material inside the mold forms Fe-Si-CO and Fe-O cast master alloys. 10g of Fe-Si-CO and Fe-O cast master alloys are cut and placed in a special quartz tube for belt spinning, and the special quartz tube for belt spinning is placed in a melting belt spinning equipment for melting. The parameters for preparing the Fe-O belt sample are: copper wheel speed 2050r / min, injection air pressure 0.002MPa, and distance from nozzle to copper wheel 0.02mm; the parameters for preparing the Fe-Si-CO belt sample are: copper wheel speed 2400r / min, injection air pressure 0.004MPa, and distance from nozzle to copper wheel 0.03mm, and the rapidly solidified Fe-Si-CO and Fe-O belt samples are prepared by the quenching belt spinning function.

2. The method for preparing a rapidly solidified iron-based alloy strip according to claim 1, characterized in that: The mass percentage of the electrolytic iron is 99.99%, the mass percentage of the single crystal silicon is 99.99%, the mass percentage of the carbon powder is 99.99%, and the mass percentage of the ferric oxide is 99.99%.

3. The method for preparing a rapidly solidified iron-based alloy strip according to claim 1, characterized in that: The ultimate vacuum degree of the smelting belt-swinging equipment is not less than 7×10 -4 Pa, the maximum smelting power is 35KVA, and the induction frequency is 30~80KHz.

4. The method for preparing a rapidly solidified iron-based alloy strip according to claim 1, characterized in that: The melting and belt-spinning equipment is a JVSM-2 high vacuum induction melting and belt-spinning machine.

5. The method for preparing a rapidly solidified iron-based alloy strip according to claim 1, characterized in that: The accuracy of the precision balance is 0.0001 mg.

6. The method for preparing a rapidly solidified iron-based alloy strip according to claim 1, characterized in that: The inner cavity size of the mold is 7. The method for preparing a rapidly solidified iron-based alloy strip according to claim 1, characterized in that: In the S2, the argon protection pressure is -0.06MPa.

8. The method for preparing a rapidly solidified iron-based alloy strip according to claim 1, characterized in that: In S3, the preset duration is five minutes.

9. The method for preparing a rapidly solidified iron-based alloy strip according to claim 1, characterized in that: The container is a magnesium oxide crucible.

10. The method for preparing a rapidly solidified iron-based alloy strip according to claim 1, characterized in that: The mold is a copper mold.

Citation Information

Patent Citations

  • Method for preparing phosphorus-containing silicon steel thin strip with high magnetic performance through melt-spinning method

    CN112846118A

  • Anti-stress amorphous nanocrystalline soft magnetic alloy and preparation method thereof

    CN112877614A

  • High-magnetic-induction iron-based amorphous soft magnetic alloy and preparation method thereof

    CN112877615A

  • Preparation method and application of iron-based nanocrystalline alloy capable of efficiently degrading dye

    CN117721361A

  • Iron-based amorphous soft magnetic alloy with single nano crystallization layer on surface and preparation method of iron-based amorphous soft magnetic alloy

    CN118064810A